Early development of immune system in pigs - Sinkora, J; Rehakova, Z; Sinkora, M; Cukrowska, B; Tlaskalova-Hogenova, H (Veterinary immunology and immunopathology, 2002)
Prenatal and early postnatal immune system development has been studied in minipigs. First leukocytes were observed in the yolk sac and fetal liver (FL) on the 17th day of gestation, the majority of them being SWC3(+). The colonization of the thymus (TH) with leukocytes was observed 21 days later. Two waves of fetal TH colonization with pro-T cells were deduced from the frequency of thymocyte subsets. Thymic B cells and immunoglobulin-secreting cells (Ig-SC) were studied by flow cytometry and ELISPOT, respectively. When the total numbers of fetal Ig-SC were compared, the TH was identified as the main source of natural antibodies and the only site of IgA and IgG synthesis. In germ-free animals, the TH also represented the major site of IgG and IgA production and the number of Ig-SC was not influenced by colonization with microflora. FL and bone marrow were identified as primary B lymphopoietic sites. The phenotype of B precursors was characterized and pre-B II cells were shown to be the dominant mononuclear fraction between DG50 and DG105. In the periphery, relative proportions of lymphocyte subsets were determined. Studies in gnotobiotic piglets have revealed that the appearance of CD4(+)CD8(+) T cells and CD2(-) B cells is absolutely dependent on the contact of immune system with live viruses and bacteria, respectively.
Keywords: buňky produkující protilátky; hematopoéza; plod; B-lymfocyty; T-lymfocyty; prasata; Swine; T-Lymphocytes; Animals, Newborn; zvířata; B-Lymphocytes; Fetus; Hematopoiesis; novorozená zvířata; Germ-Free Life; gnotobiologické modely; Antibody-Producing Cells; Animals